2012
DOI: 10.1007/s00244-012-9766-3
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Urban Mercury Contamination Detected by Bioindication With Terrestrial Isopods

Abstract: Mercury (Hg) is a trace element with high toxicological impact on potential receptors, including human beings. Global Hg emissions are predicted to increase significantly during the next 40 years. After emission, the metal is transported by air currents and precipitations, leading to increasing depositions even in areas far from emission sources. In the terrestrial environment, Hg is subjected to redistribution and transformation into different inorganic and metal-organic species that are taken up by vegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 60 publications
(68 reference statements)
0
6
0
1
Order By: Relevance
“…Con respecto a su uso como bioindicadores ambientales, especialmente en áreas urbanas, destacan estudios que han tenido en cuenta a taxones de artrópodos depredadores para evaluar la presencia de metales pesados, puesto que al encontrarse en niveles elevados de las redes tróficas los bioacumulan, como es el caso, por ejemplo, de carábidos (Coleoptera: Carabidae) (Avgin y Luff 2010) o arañas (Araneae) (Maelfait y Hendricks 1998). También se han considerado grupos de artrópodos edáficos, de carácter detritívoro o saprófago, que igualmente podrían bioacumular metales pesados al reciclar la materia orgánica en descomposición, como ácaros del suelo (Acari) (Santorufo et al 2012;Manu et al 2018), cochinillas de la humedad (Isopoda) (Pedrini-Martha et al 2012), o colémbolos (Collembola) (Santorufo et al 2012). En medios acuáticos existen estudios similares que contemplan la relación entre la perturbación de las aguas (teniendo en cuenta materiales pesados, sedimentos finos inorgánicos o concentración de oxígeno) y la variación en las poblaciones de diversos taxones de artrópodos, como, por ejemplo, efímeras, tricópteros, plecópteros y dípteros (Ephemeroptera, Trichoptera, Plecoptera y Diptera) (Relyea et al 2000), anfípodos (Amphipoda) y dípteros (Correa-Araneda et al 2010), o simplemente dípteros (Rosi-Marshall 2004).…”
Section: Los Artrópodos Como Bioindicadores Y Su Uso En áReas Urbanasunclassified
“…Con respecto a su uso como bioindicadores ambientales, especialmente en áreas urbanas, destacan estudios que han tenido en cuenta a taxones de artrópodos depredadores para evaluar la presencia de metales pesados, puesto que al encontrarse en niveles elevados de las redes tróficas los bioacumulan, como es el caso, por ejemplo, de carábidos (Coleoptera: Carabidae) (Avgin y Luff 2010) o arañas (Araneae) (Maelfait y Hendricks 1998). También se han considerado grupos de artrópodos edáficos, de carácter detritívoro o saprófago, que igualmente podrían bioacumular metales pesados al reciclar la materia orgánica en descomposición, como ácaros del suelo (Acari) (Santorufo et al 2012;Manu et al 2018), cochinillas de la humedad (Isopoda) (Pedrini-Martha et al 2012), o colémbolos (Collembola) (Santorufo et al 2012). En medios acuáticos existen estudios similares que contemplan la relación entre la perturbación de las aguas (teniendo en cuenta materiales pesados, sedimentos finos inorgánicos o concentración de oxígeno) y la variación en las poblaciones de diversos taxones de artrópodos, como, por ejemplo, efímeras, tricópteros, plecópteros y dípteros (Ephemeroptera, Trichoptera, Plecoptera y Diptera) (Relyea et al 2000), anfípodos (Amphipoda) y dípteros (Correa-Araneda et al 2010), o simplemente dípteros (Rosi-Marshall 2004).…”
Section: Los Artrópodos Como Bioindicadores Y Su Uso En áReas Urbanasunclassified
“…All this makes ‘a global woodlouse watch scheme’ (Hopkin et al 1993) even more difficult. Nevertheless, attempts to use isopods as indicators of metal pollution are still being made, as for instance shown by a study on the use of isopods as an indicator of mercury pollution (Pedrini-Martha et al 2012; Longo et al 2013).…”
Section: Isopods In Field Studies and Biomonitoringmentioning
confidence: 99%
“…Finally, a body of literature exists on the effects of pollutants, especially heavy metals on isopods. These organisms are known to accumulate heavy metals, and thus have been used as indicators of pollution levels in cities (Dallinger et al 1992, Hopkin et al 1993, Komarnicki 2005, Pedrini-Martha et al 2012).…”
Section: Research On Urban Isopods – Historymentioning
confidence: 99%
“…Isopods were proposed to use as indicators of pollution levels in cities (Dallinger et al 1992, Komarnicki 2005) and even at global scale (Hopkin et al 1993). Recently Pedrini-Martha et al (2012) showed that isopods are good indicators of mercury (Hg) contamination, while Papp et al (2018) reported significant differences in Ba and Cu concentration of Armadillidiumvulgare individuals along an urbanization gradient. Heavy metal concentration in isopod and other invertebrate tissue can be significantly affected by sampling and sample preparation protocols, which is important to keep in mind when making between-city comparisons (Zödl and Wittmann 2003).…”
Section: Terrestrial Isopods In Citiesmentioning
confidence: 99%